Repeated Interpretation: a Comparative study of Tafsir Al-Misbah and Kajian Tafsir Al-Misbah on Metro TV - MZ, Ahmad Murtaza; Hidayat, M. Riyan; Muhammad Alwi HS; Idris Ahmad Rifai (DINIKA : Academic Journal of Islamic Studies, 2022)
Throughout history, the activity of interpreting the Qur’an can be carried out either orally or through writing alone or alltogether, resulting a what so called a repeated interpretation. This article seeks to shed a light on the last mentioned type of commentary that belongs to M. Quraish Shihab, a leading mufassir whose Tafsir Al-Misbah was a reiterpreted on his oral interpretation in the program “Kajian Tafsir Al-Mishbah” on Metro TV. As samples, his commentary on QS. Al-Qalam: 1-7 is chosen. Using a critical content and comparative analysis, this study concluded that the transformation of Shihab’s commentary from written to oral form did happen through several innovations and adjustments, in terms of content and display. Thus, Shihab’s role as a skillfull preacher is still obvious in his writings although the addressed audience then becomes vague. Several factors determine the occurrence of innovation and adjustment of M. Quraish Shihab’s interpretation, namely the role of Quraish Shihab in his written interpretation as originally an exegete turned into a preacher in his oral interpretation. In addition, the context of Tafsir Al-Misbah which is intended for the wider community is different from his oral interpretation with thepresence of audiences in a more specific background.